The Impact of Regular Staff Meetings on School Belonging, Peer Learning, and Teaching Quality in Arab High Schools in Israel - Abdul Kareem Igbaria (Language, Literature and Education: Research Updates Vol. 5, 2025)
This mixed-methods study investigated the impact of bi-monthly staff meetings on organisational effectiveness in an Arab high school in Israel across three dimensions: teachers’ sense of belonging, peer learning, and teaching quality. Employing a sequential explanatory design over the 2023-2024 academic year, data were collected through surveys, interviews, focus groups, observations, and reflective journals from 49 educators. Quantitative findings revealed significant improvements in all three domains: organisational belonging (d = 0.89), peer learning (d = 1.13), and teaching quality (d = 0.79). Regression analyses identified shared decision-making opportunities (\(β\) = .46), culturally responsive discussion formats (\(β\) = .37), and recognition of professional expertise (\(β\) = .39) as significant predictors of enhanced belonging. Qualitative data revealed that meetings fostered belonging through cultural validation, collective voice, and boundary spanning. Both quantitative and qualitative data documented a three-phase developmental pattern: initial increase, plateau, and secondary increase. Culturally responsive meeting components proved particularly effective, with cultural congruence mediating the relationship between meeting participation and organisational belonging. The findings suggest that properly structured and culturally responsive staff meetings can simultaneously strengthen professional development and cultural identity in minority educational contexts, challenging the false dichotomy between cultural preservation and educational advancement. These results contribute to theories of professional learning communities, social capital, and culturally responsive pedagogy, while providing practical guidance for educational leaders in designing effective organisational structures in culturally distinctive settings.